PERAN ORANG TUA DALAM MEMBENTUK PENDIDIKAN KARAKTER ANAK DI MASA PANDEMI - Akhmad Sirojuddin; Trio Deni Adi Susanto (INCARE, International Journal of Educational Resources, 2022)
This article aims to explain the importance of maintaining character education, especially for children during a pandemic, and to find out how far the role of parents is to help maintain the success of the above objectives. This article uses the research library method by examining library data such as books, magazines, documents, historical stories, or related research objects. This character requires maximum support from the guardians of students when outside of school activities to continue to guide, direct and be a role model to behave and have noble character wherever the students are by adjusting the situation, conditions, and abilities of the child. Learning without face to face using technology is a challenge in itself for educational institutions, teachers, guardians of students, and students themselves, but in the current era, every element is required to immediately adapt and continue to be productive and force themselves to find opportunities and development for the benefit of education itself.